Effects of low-dose alcohol exposure in adolescence on subsequent alcohol drinking in adulthood in a rat model of depression - Siska, Filip; Amchova, Petra; Kuruczova, Daniela; Tizabi, Yousef; Ruda-Kucerova, Jana (The world journal of biological psychiatry, 2021)
OBJECTIVE: Adolescence drinking and subsequent development of alcohol use disorder (AUD) is a worldwide health concern. In particular, mood dysregulation or early alcohol exposure can be the cause of heavy drinking in some individuals or a consequence of heavy drinking in others. METHODS: This study investigated the effects of voluntary alcohol intake during adolescence, i.e. continuous 10% alcohol access between postnatal days (PND) 29 to 43 and olfactory bulbectomy (OBX) model of depression (performed on PND 59) on alcohol drinking in Wistar rats during adulthood (PND 80-120, intermittent 20% alcohol access). In addition, the effect of NBQX, an AMPA/kainate receptor antagonist (5 mg/kg, IP) on spontaneous alcohol consumption was examined. RESULTS: Rats exposed to 10% alcohol during adolescence exhibited a lower 20% alcohol intake in the intermittent paradigm during adulthood, while the OBX-induced phenotype did not exert a significant effect on the drinking behaviour. NBQX exerted a transient reduction on alcohol intake in the OBX rats. CONCLUSIONS: Our results indicate that exposure to alcohol during adolescence can affect alcohol drinking in adulthood and that further exploration of AMPA and/or kainate receptor antagonists in co-morbid alcoholism-depression is warranted.
Keywords: Animals; Rats, Wistar; NBQX; ethanol; pití alkoholu; Alcohol Drinking; alkoholismus; Ethanol; depression; Alcoholism; AMPA/kainate receptor; krysa rodu Rattus; Alcohol use disorder; deprese; rats; zvířata; Depression; olfactory bulbectomy; Rats; potkani Wistar